Assessing the cataloguing course in Library Information Science (LIS) programmes in Malaysia / Nurulannisa Abdullah - Abdullah, Nurulannisa (2012)
The cataloguing course offered are varies in Library Information Science (LIS) Programme in Malaysia. With the technological change every day, faculties are responsible in giving the most appropriate learning educations in preparing those students with skills and competencies and ensure what students need to know to do the jobs well. The objectives of this study are to identify the current practice of teaching and learning of cataloguing course in LIS Programme in Malaysia, to investigate the relevance of cataloguing course as perceived by educators towards professional career, to discover the required elements to improve the cataloguing courses offered and to identify the required skills and competencies of cataloguer in this technological era as perceived by the educators. A multiple case study approach is undertaken to identify the nature, level, and status of teaching cataloguing courses in five (5) LIS Programmes in Malaysia. The interviews, document analysis as well as observations are used as a method of data collection. The findings from these cases lead the researcher to generate the factors for improvement of cataloguing course framework. In summary, current practice, educators’ perceptions towards professional career, elements for improvement and required competencies as a factors in improving the cataloguing courses in all LIS Programmes in Malaysia. The finding also demonstrates that cataloguing still relevant and will continue to be taught and remain a core course even with the advent of Information Communication and Technology (ICT) that revolutionised information organisation in the past decade. The results of the study has provided input to the LIS Programmes in Malaysia in reviewing the course content, examined the course offering as well as described teaching philosophy since the technology changes and give impact to the world of librarianship nowadays. The study has helped the faculty member to prepare some initiative in order to give graduates become capable of using whatever standards are appropriate to manage and organise information in the networked environment.